Does the PBL-RQA Model Improve Students' Information Literacy and Self-Confidence? - Pratiwi, Rifanissa Eka; Zubaidah, Siti; Novianti, Vivi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Several studies show that students' information literacy and self-confidence are still low and need to be improved. Students find the biological material on the digestive and respiratory systems particularly challenging because it explains the complex interactions between the structure, function, and symptoms of the disorders these systems cause and their uncommon scientific names. This study determined how Problem-Based Learning integrated with the Reading, Questioning, and Answering (PBL-RQA) model affects students' information literacy and self-confidence. Using a quasi-experimental with a nonrandomized control-group pretest-posttest design, 96 students from junior high school in Bangkalan Regency, East Java, Indonesia were sampled for the study. They were divided into one experimental class and two control classes. The PBL-RQA model was taught in the experimental class, while the PBL and RQA models were each taught in the control class. Information literacy was acquired through an essay test, and self-confidence was acquired through a questionnaire given using Google Forms. The analysis was conducted using the ANCOVA test with a significance level of 5% and then followed up with the least significant difference test. Students in the PBL-RQA class achieved the highest mean scores in information literacy and self-confidence, with 79.19 and 78.50, respectively. Based on the results, PBL-RQA learners significantly increased information literacy and self-confidence than PBL and RQA.